2008
DOI: 10.1590/s0366-69132008000200011
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and characterization of rice husk silica, silica-carbon composite and H3PO4 activated silica

Abstract: This paper discusses synthesis and characterization of (i) rice husk based nanosilica, (ii) nanosilica carbon composite granules and (iii) phosphoric acid activated ash silica. These have been produced by burning husk in air, charring husk in hydrogen and activating husk silica with H3PO4 respectively. X-ray diffraction studies of these products reveal increasing peak width (amorphosity) with decreasing burning temperature. The activated rice husk silica transforms to crystalline product when burnt above 1000 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
21
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(25 citation statements)
references
References 15 publications
3
21
0
1
Order By: Relevance
“…The existence of the ZrSiO 4 phase in the fired ceramic shell mould are due to the formation of amorphous fused silica after firing rice husk at low temperature (below 1000 ºC) in air. In fact, the amorphous fused silica also was proved can combine and harden the brittle ceramic structure [7,19]. Although similar results were obtained in works by Javed et.…”
Section: Advanced Materials Research Vol 795mentioning
confidence: 54%
See 1 more Smart Citation
“…The existence of the ZrSiO 4 phase in the fired ceramic shell mould are due to the formation of amorphous fused silica after firing rice husk at low temperature (below 1000 ºC) in air. In fact, the amorphous fused silica also was proved can combine and harden the brittle ceramic structure [7,19]. Although similar results were obtained in works by Javed et.…”
Section: Advanced Materials Research Vol 795mentioning
confidence: 54%
“…Although similar results were obtained in works by Javed et. al, the silica were found to be in crystalline form which is stable until up to 1700 ºC [19][20]. ZrSiO 4 phase is known to have low thermal expansion coefficient and is highly resistant to thermal shock [21].…”
Section: Advanced Materials Research Vol 795mentioning
confidence: 99%
“…In all biomaterials, a peak is observed within the ranges from 15° to 30°, indicating disordered structure. XRD analysis of the feedstock and biochars confirmed the presence of amorphous silica as indicated by the heap at 2θ ~ 22.5 o idue to amorphous silica and quartz amorphous silica, which is a major constituent of these biomaterials, can be present in form of disordered cristobalite (SiO 2 ) (Singh et al, 2008 andSrivastava et al, 2006). Chemical properties: Table 2 shows that, on the average, the pH value of SCBBs lower than in the RHBs.…”
Section: -Feed Stock Propertiesmentioning
confidence: 92%
“…The X-ray spectrum of the prepared silica structures shows a single, broad peak at 2h = 21°-22° [25]. This broad peak was indicated that the silica framework is amorphous [26,27]. X-ray diffraction patterns of functionalized silica indicate that the structure of amino functionalized silica and coumarin based silica showed also a typical porous and amorphous structure.…”
Section: Characterization Of Coumarin Functionalized Porous Silicamentioning
confidence: 95%